Degenerate nonselfadjoint high-order ordinary differential equations on an infinite interval - L. P. Tepoyan; S. Zschorn (Հայաստանի ԳԱԱ)
The paper considers the generalized Dirichlet problem for a class of degenerate nonselfadjoint high-order ordinary differential equations on an infinite interval.
Keywords: Mathematics; Science